Making agricultural value chains more inclusive through technology and innovation - Reena Das Nair; Namhla Landani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Some entry barriers in agricultural and agro-processing value chains, particularly for smallholder farmers and small/medium-sized processors, can be overcome with innovation and technology adoption. Technologies and innovation in these sectors have been both radical and incremental, ranging widely through biotechnology; production technologies; automation in sorting, grading, and packaging; and digital platforms and data-connected devices for market access. These technologies have enabled farmers in Africa to increase productivity and quality; reduce costs; meet standards; improve access to finance, markets, and information; and facilitate payments. We evaluate the role of technology in South African fresh fruit and selected processed food value chains in facilitating inclusive participation, while highlighting potential adverse effects for certain players. Recommendations for addressing the challenges and building capabilities to adopt new technologies are provided, emphasizing the role for public-private partnerships and an enabling regulatory environment.
Keywords: O13; O14; O30; O31; Q16; 330; innovation; technology; upgrading; value chains; agriculture; agro-processing; inclusive; capabilities